The impact of the Social Security Fund on auditor litigation risk - Lei Zhu; Qianwen Zheng (China Journal of Accounting Research, 2020)
In this study, we examine the effect of the Social Security Fund on auditor litigation risk. Using audit fees as a proxy for auditor perceptions of litigation risk, we find that the Social Security Fund significantly reduces auditor litigation risk. Furthermore, we show that the Social Security Fund influences auditor litigation risk through reducing both the audit risk and the business risk of public companies. In addition, the impact of the Social Security Fund for reducing auditor litigation risk is more obvious in the group of firms with low levels of internal governance, which indicates that the Social Security Fund plays an important governance role as a high-quality institutional investor. In summary, we verify that the Social Security Fund, when acting as an institutional investor, plays an important role in corporate governance, and that it helps to reduce auditor litigation risk. Our results provide empirical support for expanding the governance role of the Social Security Fund as an institutional investor in China's A-share market.
Keywords: 650; Auditor litigation risk; External corporate governance; Institutional investors; Social Security Fund